Can oral communication strategies help improve oral presentation skills? - Idrus, H. (American Scientific Publishers, 2017)
The purpose of this study is to identify the communication strategies used by English as a Second Language (ESL) students while delivering oral presentations in an oral communication skills course. Thus, the Oral Communication Strategies Inventory (OCSI) was used to access strategies that the students used for dealing with communication problems while delivering their oral presentations. The OCS inventory included eight categories of strategies for coping while speaking and seven categories of strategies for coping while listening. The respondents were 100 ESL students enrolled in a communication skills course. Results of the data analysis revealed that the high competency presenters employed more communication strategies than the average presenters. The high competency students had more frequently used social-affective, fluency-oriented, and non-verbal strategies for coping with speaking problems. The average students, on the other hand, do utilize the social affective and non-verbal strategies but on a much lesser degree but they also employed the reduction or avoidance strategies. Regression analysis was used to explain the relationship between communication strategies used by the students and the grades they obtained. The findings suggest that average students should be made aware of the mentioned skills and be familiarized with them in order to further develop their oral presentation skills. Hence, oral communication strategies can help students enhance their oral presentation skills if they employ the right strategies. © 2017 American Scientific Publishers. All rights reserved.